Поняття адаптації в різних напрямках психології - Ніколаєнко, Св.; Ніколаєнко, О. (Світогляд - Філософія - Релігія, 2011)
У статті аналізуються положення найбільш відомих у психології теорій щодо можливостей та тенденцій адаптації до змін, які відбуваються в суспільстві, природі та світі в цілому. This article analyzes the provisions of the most famous theories in psychology to understand the nature of the human psyche, possibilities and trends of its development because of the need to adapt to changes occurring in society, nature and the world at large. As a result, it is concluded that the term “adaptation” is used in various concepts to explain the role of this process in the existence and development of mental activity and human consciousness.